2000
DOI: 10.1007/s002770000181
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis using 2′,2′difluorodeoxycytidine (gemcitabine) in combination with antimetabolites or anthracyclines on malignant lymphatic and myeloid cells. Antagonism or synergism depends on incubation schedule and origin of neoplastic cells

Abstract: Induction of apoptosis in vitro using gemcitabine (dFdC) in combination with cladribine (2-CdA) and other cytotoxic drugs on malignant mononuclear cells (MNCs) of patients with acute myeloid leukemia (AML, n=20) and chronic lymphocytic leukemia (CLL, n =20) in myeloid (HL60, HEL) and lymphatic cell lines (HUT78, JURKAT) was investigated using different incubation conditions (simultaneous and consecutive). Furthermore, the influence of dFdC on the level of intracellular metabolites of 2-CdA was studied using hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…The fraction affected (Fa) (i.e. Fa of 0.25 is equivalent to 75% viable cells) and the combination index (CI) were calculated with CalcuSyn (Chow et al, 2000). This method enables quantification of synergism (CIo1) and antagonism (CI41) at different dose and effect levels.…”
Section: Concurrent Exposure To Zol and Other Anticancer Agentsmentioning
confidence: 99%
“…The fraction affected (Fa) (i.e. Fa of 0.25 is equivalent to 75% viable cells) and the combination index (CI) were calculated with CalcuSyn (Chow et al, 2000). This method enables quantification of synergism (CIo1) and antagonism (CI41) at different dose and effect levels.…”
Section: Concurrent Exposure To Zol and Other Anticancer Agentsmentioning
confidence: 99%
“…In those studies, only gemcitabine was given on day 1, whereas on day 8 gemcitabine preceded TXT, a sequence that was synergistic in an osteosarcoma and a breast cancer cell line (Leu et al, 2004); however, in lung cancer cell lines, the opposite sequence was more effective (Zoli et al, 1999). Similarly, in vitro studies have shown that the effects of a combination of DXR and gemcitabine depend both on the sequence of administration and on the particular cell line studied (Chow et al, 2000;Zoli et al, 2004). The administration of gemcitabine followed by DXR, or the delivery of DXR on day 8, would perhaps offer a better therapeutic index than the present schedule, which cannot be recommended for further study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the different mechanisms of action of the two drugs, which have been shown to synergise in in vitro and in vivo models (Chow et al, 2000;Gallo et al, 2006), as well as the nonoverlapping toxicity profiles, further strengthened the rationale for their combination. Indeed, combined administration of PLD/GEM has been successfully investigated in ovarian cancer (Ferrandina et al, 2005), as well as in recurrent/metastatic breast cancer patients; in particular, in the latter subset of patients, an overall response rate between 26 and 52% (median duration of response ¼ 5.5-7 months), with an acceptable toxicity profile, has been reported in three phase II studies (Rivera et al, 2003;Fabi et al, 2006;UlrichPur et al, 2007).…”
mentioning
confidence: 99%